Evaluation of the epidemiological profile and output indicators of the Tuberculosis Control Program (Research, Society and Development, 2020)
Objective: Evaluate the epidemiological profile and outcome indicators of the tuberculosis control program in the municipality of Guanambi, Bahia, between 2010 and 2018. Methods: Analytical epidemiological retrospective cohort study. Data collection was performed in the Notification Disease Information System (SINAN) and in the municipality’s department of the Tuberculosis Control Program. Descriptive analysis was performed with frequencies and percentages for categorical, mean and standard deviation variables for age. Then the result indicators for the municipality were calculated. Results: From 2010 to 2018, 88 cases of tuberculosis were reported, highlighting the prevalence in men with an average age of 49.9 years, low education and brown race, where 89,7% of cases were cured, 2.3% were transferred, 1.1% had a change in diagnosis, 1.1% died, 8.0% were in progress at the time of data collection and 2.3% had no information. The most positive indicators of the Municipality in the period were: closed cases (0.96), cured cases (0.91), bacteriologically confirmed new cases (0.86), contacts examined among the registered cases (0.86) and cases tested for HIV (0.85). The municipality had low rates of abandonment of new cases (0.00), cases closed with death (0.01) and retreatment cases (0.08). Conclusion: It has been evidenced that the numbers of tuberculosis cases have been stabilized in recent years, and that the treatment has been effective.